2021
DOI: 10.7759/cureus.13381
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Admission Service Triage (H-FAST) Study: Racialized Differences in Perceived Patient Self-Advocacy as a Driver of Admission Inequities

Abstract: Background Racial inequities in mortality and readmission for heart failure (HF) are well documented. Inequitable access to specialized cardiology care during admissions may contribute to inequity, and the drivers of this inequity are poorly understood. Methodology This prospective observational study explored proposed drivers of racial inequities in cardiology admissions among Black, Latinx, and white adults presenting to the emergency department (ED) with symptoms of HF. Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Next, differences in receipt of a single organ could also be related to disparities in healthcare self‐advocacy, health literacy, and mistrust in the medical system among Black patients. White patients are generally more likely to advocate for themselves in healthcare settings [29] and demonstrate higher levels of health literacy compared to Black patients [30]. Research has revealed that higher levels of health literacy can mediate the relationship between socioeconomic status and health disparities [31].…”
Section: Discussionmentioning
confidence: 99%
“…Next, differences in receipt of a single organ could also be related to disparities in healthcare self‐advocacy, health literacy, and mistrust in the medical system among Black patients. White patients are generally more likely to advocate for themselves in healthcare settings [29] and demonstrate higher levels of health literacy compared to Black patients [30]. Research has revealed that higher levels of health literacy can mediate the relationship between socioeconomic status and health disparities [31].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of region-related factors, Novinger et al [18] conducted a survey in the elderly population, and the results showed that the self-advocacy ability of the elderly in urban areas is generally higher than that in rural areas, and the reasons may be related to the higher education level, higher economic level, more social resources, and richer information channels of the elderly in urban areas. In addition, Cleve et al [19] have shown that white people are more able to put forward their own needs and achieve self-advocacy. In terms of disease severity, Hagan et al [20] found that the severity of the patient's condition is positively correlated with self-advocacy ability, which may be due to the fact that when the patient's condition is urgent and serious, the communication with medical personnel is increased, which can indirectly increase the knowledge of the disease.…”
Section: General Demographic Datamentioning
confidence: 99%
“…A prior phase of our work evaluated the root causes for the disparities in initial admission triage of CHF patients 19 . In the study reported here, we aimed to use the Public Health Critical Race Praxis (PHCRP) framework to engage our QI teams, in collaboration with key stakeholders, in designing a QI initiative that addressed the barriers and needs of racial and ethnic subpopulations within an overall effort to improve outcomes for patients triaged to GMS.…”
Section: Introductionmentioning
confidence: 99%